The epidemiology of carbapenem-resistant Enterobacterales in a single center in Oman - AL Yarabi, Ahmed; AL Maskari, Zaina; AL Tai, Amal; Khamis, Faryal; Petersen, Eskild; AL Jardani, Amina (International Journal of Infection Control, 2023)
Background: Carbapenem-resistant Enterobacterales (CRE) are a global public health threat associated with significant morbidity and mortality. Objectives: The study aims to describe the epidemiology, microbiology and outcome of patients with CRE infection or colonization during an active surveillance program and to determine the risk factors for the acquisition of such organisms in a single center in Oman. Method: A retrospective case–control study was conducted in a tertiary care hospital in 2015 and 2016. Cases included patients who had a positive screening or clinical sample for CRE and controls included patients who were screened during the same period and never had a positive screening or clinical sample for CRE. Risk factors analyzed were demographics, comorbidities, instrumentation, and antibiotic exposures. Data were analyzed using SPSS for Windows (version 11.5). Variables of interest were analyzed by univariate analysis, and those of significance were analyzed by logistic regression. Results: Seven hundred and twenty-eight cases were detected from active surveillance screening, and clinical samples and 749 controls were included. Males comprised 417 (57.3%) cases and females 311 (42.7%). The majority of CRE cases were adult patients (88%, n = 644) compared to 12 % (n = 84) paediatric. The total number of CRE screenings was 8,431 samples in 2015 with a positivity rate of 4.2% and 10,231 samples in 2016 with a positivity rate of 3.6%. The annual incidence rate of CRE was 0.8 per 100 admissions in 2015 and 0.76 per 100 admissions in 2016. The annual incidence density was 1.90 and 1.89 per 1000 patient days for both years, respectively. Healthcare-associated acquisition was 99.5%, and only 0.5% was attributed to the community. The most common sites of infections were urine and wound comprising 29% each. Klebsiella pneumoniae (n = 578, 79%) was the predominant organism followed by Escherichia coli (n = 101, 14%). CRE acquisition was significantly associated with the presence of a urinary catheter (odds ratio [OR]: 7.3; confidence interval [CI]: 4.6–11.6; P < 0.0001 or central line (OR: 3.5; CI: 2.068–6.011; P < 0.001), intubation (OR: 0.5; CI: 0.264–0.947; P < 0.034), antibiotic exposure (OR: 4.5; CI: 3.101–6.586; P < 0.0001), and intensive care unit (ICU) admission (OR: 0.5; CI: 0.297–0.852; P = 0.011). In addition, history of a local and an abroad hospital admission significantly increased the risk of CRE acquisition (respectively, local OR: 10.97; CI: 7.878–15.301; P < 0.000, abroad OR: 12.4; CI: 6.597–23.617; P < 0.0001). Overall mortality was 23.1 and 52.3% among bacteremia cases. Conclusion: The annual incidence of CRE acquisition is high with a high mortality rate. A multifaceted strategy to control the spread of CRE is fundamental, considering the specific epidemiology of CRE related to our institution and country.